Effect of Sofosbuvir plus Ribavirin therapy on hepatitis C patients in Pakistan: a retrospective study - Zubia Jamil; Yasir Waheed; Maryam Malik; Asghar A. Durrani (PeerJ, 2018)
Background The annual global deaths from viral hepatitis is 1.4 million. Pakistan has the second highest burden of hepatitis C in the world. There is dire need to evaluate the response of new direct acting antivirals for the treatment of hepatitis C patients in Pakistan. World Health Organization has developed a strategy to treat 80% of HCV patients by 2030. In Pakistan, HCV treatment rate is 1%. The aim of the study was to analyze the effect of Sofosbuvir plus Ribavirin therapy on HCV patients in Pakistan. Methods An observational study was conducted at Fauji Foundation Hospital Rawalpindi from November-2016 to July-2017. All the drugs were administered according to the guidelines of Asia Pacific Association for the Study of Liver (APASL) for the treatment of HCV patients. A total 327 chronic HCV patients were enrolled in the study and 304 completed the treatment. Patients belonged to three different groups including treatment: Naïve patients (n = 107), Non-Responder patients (n = 126) and patients who relapsed to Interferon therapy (n = 71). All the patients were given Sofosbuvir plus Ribavirin therapy for 24 weeks and the early virological response (EVR) and end treatment response (ETR) was calculated. Different parameters including patient age, viral load, viral genotype, blood picture, ultrasound findings and liver function tests were also studied. Results Out of 304 patients, 301 (99%) achieved EVR and 300 achieved ETR (98.7%). End treatment response was 95.6% in HCV genotype 1 and 98.9% in HCV genotype 3 patients. ETR was 99.06% in treatment Naïve, 99.20% in non-responders and 97.18% in previously relapsed patients. We did not find the association of any host and viral factor in the determination of EVR and ETR. Conclusion The Sofosbuvir plus Ribavirin treatment is highly effective, safe and cost-effective for the treatment of hepatitis C patients in Pakistan.